Mutualismo Ferroviário: prover e proteger na Sociedade Beneficente do Pessoal da Estrada de Ferro de Baturité de 1891 aos anos 1930 - Mota, Kleiton Nazareno Santiago (2009)
The objective of this research is to analyze the experience of the formation, restructuration and development of the Baturite’s Railroad Charity Society, pointing the action of railroad workers in the mutual’s benefit composition offered. This experience show us that the Society was constituting itself as a way of betterment of life for the workmen, having the health, education and the access to loans and judiciary assistance as their point of support. The study chronological landmarks are delimited between the creation of Charity Society in 1891 and the 1930’s, when start to be felt the effects of the Eloy Chaves Law, promulgated in 1923, that created the Account of Retirements and Pensions, inaugurating the social security promoted by the State in Brazil.